Institutionalizing passion in world politics: fear and empathy. Issue 3 (9th October 2014) - Crawford, Neta C.
<x content-type="archive" xml:space="preserve">Abstract</x> Emotions are a ubiquitous intersubjective element of world politics. Yet, passions are often treated as fleeting, private, reactive, and not amenable to systematic analysis. Institutionalization links the private and individual to the collective and political. Passions may become enduring through institutionalization, and thus, as much as characterizing private reactions to external phenomena, emotions structure the social world. To illustrate this argument, I describe how fear and empathy may be institutionalized, discuss the relationship between these emotions, and suggest how empathy may be both a mirror and potential antidote to individual and institutionalized fear.